2014
DOI: 10.1155/2014/304250
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Vitamin D Deficiency and Vitamin D Receptor Genotypes on the Degree of Collateralization in Patients with Suspected Coronary Artery Disease

Abstract: We determined the association of vitamin D deficiency and the FokI polymorphism of the vitamin D receptor (VDR) gene in 760 patients who underwent angiography due to suspected coronary artery disease (CAD). Angiography and the Rentrop scoring system were used to classify the severity of CAD in each patient and to grade the extent of collateral development, respectively. Polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) was used to determine the FokI VDR gene polymorphism. The preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 44 publications
(52 reference statements)
1
26
0
1
Order By: Relevance
“…Of the 272 excluded studies, 44 were duplicate publications; 196 were not relevant to VDR gene polymorphisms and CAD risk; 12 were reviews, editorials, or comments; 4 were case reports; 5 were studies that reported on the association between other polymorphisms of the VDR gene and CAD risk; 4 were on patients with diabetes or kidney disorders; 2 were studies without any control group; and 8 were other irrelevant articles. A total of 8 relevant studies (cases, 5,259; controls, 1,981) were finally included based on the inclusion criteria for CAD susceptibility related to the Fok I, Bsm I, Taq I, and Apa I polymorphisms [24,25,26,27,28,29,30,31,32]. Of these, 7 studies were performed in Caucasians [24,25,26,27,29,30,32], and 2 studies [28,31] were performed in East-Asians.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 272 excluded studies, 44 were duplicate publications; 196 were not relevant to VDR gene polymorphisms and CAD risk; 12 were reviews, editorials, or comments; 4 were case reports; 5 were studies that reported on the association between other polymorphisms of the VDR gene and CAD risk; 4 were on patients with diabetes or kidney disorders; 2 were studies without any control group; and 8 were other irrelevant articles. A total of 8 relevant studies (cases, 5,259; controls, 1,981) were finally included based on the inclusion criteria for CAD susceptibility related to the Fok I, Bsm I, Taq I, and Apa I polymorphisms [24,25,26,27,28,29,30,31,32]. Of these, 7 studies were performed in Caucasians [24,25,26,27,29,30,32], and 2 studies [28,31] were performed in East-Asians.…”
Section: Resultsmentioning
confidence: 99%
“…There were 6 studies [26,27,28,29,31,32] with 2,823 cases and 1,072 controls concerning the Fok I polymorphism and CAD risk; among them, 4 studies were performed in Caucasians [26,27,29,32], and 2 studies were performed in East-Asians [28,31] (Tables 1, 2). For this polymorphism, the studies by O'Halloran et al [27] and Abu el Maaty et al [32] deviated from HWE.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it was suggested that the F variant is more effective than the f variant as a transcription factor. Individuals carrying the Ff and ff genotype had significantly lower concentrations of vitamin D compared to patients with the FF genotype …”
Section: Genotype and Allele Frequencies Of Vdr Bsmi B/b And Foki F/fmentioning
confidence: 90%
“…Several studies have been executed in different populations to decipher the role of VDR polymorphisms in T2D [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] and CAD. [40][41][42][43][44][45] To the best of our knowledge, studies on the importance of vitamin D or VDR polymorphisms in T2D patients with CAD are lacking. In the present study, we enrolled patients with T2D from the Chinese cohort and investigated the importance of vitamin D and VDR in patients with T2D concerning CAD.…”
Section: Introductionmentioning
confidence: 99%